1993
DOI: 10.1042/cs0850077
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Butyrylcholinesterase Activity, Hypertriglyceridaemia and Insulin Sensitivity in Diabetes Mellitus

Abstract: 1. The activity of serum butyrylcholinesterase ('pseudocholinesterase', EC3.1.1.8) was investigated in 56 patients with type 1 diabetes mellitus, 51 patients with type 2 diabetes mellitus and 101 healthy control subjects. 2. Butyrylcholinesterase activity was significantly elevated in both type 1 (8.10 +/- 3.35 units/ml) and type 2 (7.22 +/- 1.95 units/ml) diabetes compared with the control subjects (4.23 +/- 1.89 units/ml) (P < 0.001). 3. In the patients with type 1 and type 2 diabetes, serum butyrylcholinest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 0 publications
2
50
1
1
Order By: Relevance
“…An earlier study (21) showed that the mean values of BChEA in DM1 and DM2 were not significantly different. However, this result was not replicated in the present study.…”
Section: Butyrylcholinesterase and Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study (21) showed that the mean values of BChEA in DM1 and DM2 were not significantly different. However, this result was not replicated in the present study.…”
Section: Butyrylcholinesterase and Diabetes Mellitusmentioning
confidence: 99%
“…(21), studying the relationship between BChEA and hypertriglyceridemia in DM1 and DM2 patients and in patients with impaired glucose tolerance, found a positive correlation between BChEA and the logarithm of fasting TG serum levels, and that BChEA also positively correlates to insulin resistance in DM2 patients. They concluded that BChE may play a role in the development of hypertriglyceridemia in DM, associated with the resistance to or deficiency of insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of a specific inhibitor of BuChE after induction of diabetes in these animals also reversed hypertriglyceridemia [13]. In a study on patients with diabetes type I or type II, BuChE activity correlated positively with TG concentration and inversely with insulin sensitivity [14]. 10 Our results show that chronic treatment with GL caused a significant decrease of HDL-cholesterol by 19% and 32% after 6 and 12 weeks of treatments (Table 1).…”
Section: Discussionmentioning
confidence: 49%
“…High BuChE activities are typical for patients with hypercholesterolemia, hypertension, obesity and Type I or Type II diabetes [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Venkata et al [18] found that pseudo-cholinesterase concentration decreased correspondingly and specifically with more functional liver cell damage. Other studies [19,20] found that plasma cholinesterase had relationship with triglycerides, HDL-C, and LDL-C. More recent reports [10,11,21,22] extended the association to wide range of variables with the metabolic syndrome including body mass index, apolipoprotein concentrations, insulin, liver enzymes, and blood pressure. Moreover, Nyblom et al [23] reported that the SGOT/ SGPT ratio can be used as an indicator of cirrhosis in alcoholic liver disease, hepatitis C and supported that the high ratio ([1.1) actually reflects cirrhotic changes in the liver.…”
Section: Discussionmentioning
confidence: 94%